90 Predictors of Mortality in Patients with Hypertrophic Cardiomyopathy - A Hospital Admissions Study: 2000-2013. (31st May 2014) - Khouw, Niece; Wasim, Mohammad; Uppal, Hardeep; Chandran, Suresh; Potluri, Rahul
Abstract : Introduction: Hypertrophic Cardiomyopathy (HCM) is a rare condition that can be associated with sudden cardiac death. The predictors of mortality in patients with HCM have not been well studied. Objectives: The aim of this study is to investigate the predictors of mortality in patients with HCM from a large sample of hospital admissions. Methods: Anonymous information on patients with Hypertrophic Cardiomyopathy, co-morbidities and procedures attending large multi-ethnic general hospitals in Manchester, United Kingdom in the period 2000–2013 was obtained from the local health authority computerised hospital activity analysis register using ICD-10 and OPCS coding systems. Statistical analysis was performed using SPSS version 20. Results: Out of 1, 221, 216 patients admitted, there were 253 patients with HCM. The mean age of 55.8 years ± 18.8(S.D) with 63.2% male patients VS 36.8% female patients. The main co-morbidities were Hypertension (86;34.0%), Atrial Fibrillation (69;27.3%), Heart Failure (27;10.7%), Type 2 Diabetes Mellitus (24;9.5%), Ventricular Tachycardia (16;6.3%), Defibrillator Implant (16;6.3%). A multi-nominal logistic regression model accounting for variations in age, sex and ethnic group showed that only Atrial Fibrillation (RR3.8;C.I1.7–8.1) and Heart Failure (RR5.0;C.I1.9–13.5) are significant predictors of mortality (p < 0. 05). Conclusion: We have shown that Atrial Fibrillation and Heart Failure are significant predictors of mortality in patients with HCM from a large hospital based sample in the UK. This reflects the known complications of HCM affecting mortality. However, it is surprising that Defibrillator implantation does not confer improved mortality. Our improved understanding of these predictors will guide clinicians to focus on these high risk groups to improve clinical practice and outcomes in patients with HCM.